The origin of competitive dialogue and its adoption in the Brazilian legal order - Bertoncini, Mateus; Rocha, Luiz Felipe da; Díaz, Juan Francisco (Revista Seqüência: Estudos Jurídicos e Políticos, 2024)
This article aims to analyze the origin of Competitive Dialogue and the way it was adopted in the Brazilian legal system through Law 14,133/2021. The study covers the origin of the new bidding modality inserted in Brazilian legislation, which has its embryo in Europe, through the Green Book, which is a Communication adopted by the European Commission on November 27, 1996, being a documentary landmark in dealing with a greater rapprochement between the Public Power and the private sector when carrying out public contracts. With the advent of Directive 2004/18/EC of the European Parliament and of the Council, which dates from 31 (thirty-one) March 2004, competitive dialogue expressly emerged. This Directive was revoked and succeeded by Directive 2014/24/EU of the European Parliament and of the Council on 26 (twenty-six) February 2014, which maintained the “competitive dialogue” in its provisions and improved its discipline. Examples of countries that have internalized competitive dialogue in their legal systems, the legislative process for internalizing the institute in the Brazilian legal system and its legislation in Brazilian law and comparative law are also discussed. For the construction and development of the theme, the positions of respected scholars and theorists were addressed, as well as the letter of the law itself, which enable an accurate analysis of the aforementioned topic, and, therefore, the methodology of the study is the research of legislation and doctrine regarding of the theme.